2018
DOI: 10.1016/j.eats.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Untethering of the Fat Pad of the Knee: Release or Resection of the Infrapatellar Plica (Ligamentum Mucosum) and Related Structures for Anterior Knee Pain

Abstract: Anterior knee pain (AKP), a multifactorial symptom complex, can be successfully treated surgically. A specific diagnosis often cannot be made, but the pain is linked to an unrecognized common factor in most patients: the mechanical behavior of the non-isometric contents of the anterior compartment of the knee—the fat pad (FP) and infrapatellar plica (IPP). The objective of this presentation is to describe an effective arthroscopic technique that treats AKP by addressing this common factor. The operation consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…There are several studies with findings similar to this study regarding symptomatic infrapatellar fat pad fibrosis. The previous studies reported that anterior interval fibrosis might cause anterior knee pain [28], and that good outcomes can be obtained after the release of anterior scar tissue [20, 25, 27]. Fibrosis of the anterior interval can be caused by trauma to the infrapatellar fat pad via direct injury to the ACL or patellar tendon or by iatrogenic injury due to the creation of arthroscopy portals and post‐ACL reconstruction scarring associated with tendon harvest or fat pad resection [2, 12, 26].…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies with findings similar to this study regarding symptomatic infrapatellar fat pad fibrosis. The previous studies reported that anterior interval fibrosis might cause anterior knee pain [28], and that good outcomes can be obtained after the release of anterior scar tissue [20, 25, 27]. Fibrosis of the anterior interval can be caused by trauma to the infrapatellar fat pad via direct injury to the ACL or patellar tendon or by iatrogenic injury due to the creation of arthroscopy portals and post‐ACL reconstruction scarring associated with tendon harvest or fat pad resection [2, 12, 26].…”
Section: Discussionmentioning
confidence: 99%
“…4,13 Its size can range from a thin band to a broad membrane. 2 Posteriorly, it may be either continuous or separated from the anterior cruciate ligament (ACL), 13,41 and it may even encircle the ACL to divide the inferior aspect of the knee joint into two separate compartments. 2 An insertion to the medial surface of the lateral femoral condyle was also described.…”
Section: Infrapatellar Plicamentioning
confidence: 99%
“…42 A more horizontal course was also reported. 41 The infrapatellar plica poses some nuisance during arthroscopy. When the plica manifests as a complete septum, it can prevent the arthroscope from being passed between the medial and lateral compartments of the knee.…”
Section: Infrapatellar Plicamentioning
confidence: 99%
See 2 more Smart Citations